A new species of Diplycosia (Ericaceae) from Mount Jaya, western New Guinea - Mustaqim, Wendy A.; Chikmawati, Tatik; Utteridge, Timothy M.a.; Heatubun, Charlie D. (Phytotaxa, 2020)
Diplycosia puradyatmikai, a new species of Ericaceae, is described from Mount Jaya in the Indonesian province of Papua, western New Guinea. A detailed description, illustration, and comparisons with the similar species D. kosteri are provided.